Smart Dakwah di Era Society 5.0 ; Da'i Virtual dalam New Media - Vyki Mazaya (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
The era of Society 5.0 gave rise to a new tradition in the use of technology as problem solving in all aspects of life in order to provide convenience for society, including in overcoming religious problems. The activity of studying (deepening religious knowledge) switched to studying virtually through new media. The ease of accessing new media is one of the advantages but da'wah content in new media is brought by da’i who have diverse patterns. The concern is the spread of da'wah content that is exclusive because it triggers the disintegration of religious people and radicalism considering that Indonesians are mostly users of smartphones and social media but the literacy rate is very low in the world. Smart da'wah efforts are needed as an adaptive step in the era of society 5.0 by prioritizing moderate (inclusive) Islamic content by considering various elements in da'wah. The number of da'wah influencers as content creators who do not have the depth of Islamic religious knowledge but have a spirit in spreading goodness (da’i muqallid) in new media becomes a positive thing. However, mad'u needs to understand the level of da’i and choose the content to be used as a reference from da’i which has the level of da’i mujtahid or da’i muttabi'. Mastery of technology and skills in packaging da'wah content is needed for virtual da’i in new media so that da'wah content uploaded in new media can attract mad'u. SWOT analysis is needed to carry out da'wah in the era of society 5.0.